Thyroid Dysfunction And Renal Biomarkers During Pregnancy: Comparative Insights Into Tsh And Creatinine Levels - T V, Shylaja; A Natikar, Jyothi; Gujral, Jaspreet Kaur; Arya, Alok Kumar; G, Asha; Simlai, Sankha (Journal of Neonatal Surgery, 2025)
Background: Pregnancy induces numerous physiological adaptations, particularly in the endocrine and renal systems. Thyroid dysfunction—especially hypothyroidism—alters maternal and fetal outcomes, and its interplay with renal function remains under-investigated. Objective: To compare TSH and serum creatinine levels between euthyroid and hypothyroid pregnant women and to explore any correlation between thyroid status and renal function. Methods: A cross-sectional study was conducted on 100 pregnant women (50 hypothyroid, 50 euthyroid controls). TSH and serum creatinine levels were measured using standardized methods. Statistical significance was determined with SPSS version 20. Results: Mean TSH was significantly higher in euthyroid women (2.37 ± 0.85 µIU/ml) compared to hypothyroid women (1.05 ± 0.80 µIU/ml; p=0.006). Serum creatinine was significantly elevated in hypothyroid women (0.80 ± 0.45 mg/dL) vs. controls (0.55 ± 0.16 mg/dL). A statistically significant inverse relationship between TSH and serum creatinine was observed. Conclusion: Hypothyroid pregnant women exhibit elevated serum creatinine, indicating early renal impairment. Co-monitoring of thyroid and renal biomarkers may improve maternal-fetal outcomes